2020
DOI: 10.46328/ijemst.v8i4.952
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion & Marginalization: How Perceptions of Design Thinking Pedagogy Influence Computer, Electrical, and Software Engineering Identity

Abstract: Engineering identity plays a vital role in the persistence of engineering students, yet limited research exists on how particular pedagogical approaches influence engineering identity at the college level. This qualitative case study explored how undergraduate student perceptions of design thinking pedagogy influence computer, electrical, and software engineering identity. The study found that design thinking pedagogy reinforces the recognition of an engineering identity, particularly for those from historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…38 It is to transform the abstract into the physical. 44 Rodriguez et al 45 investigated how DT influences the identities of undergraduate engineering students and argue that if well implemented, students from marginalized groups can have positive results because it allows this group to connect with their course by incorporating their interests and enabling visualization of them in their role. The authors acknowledge a limitation of the research, which necessitates a longitudinal investigation, whereby data must be collected continuously or repeatedly over an extended duration.…”
Section: Background and Related Workmentioning
confidence: 99%
“…38 It is to transform the abstract into the physical. 44 Rodriguez et al 45 investigated how DT influences the identities of undergraduate engineering students and argue that if well implemented, students from marginalized groups can have positive results because it allows this group to connect with their course by incorporating their interests and enabling visualization of them in their role. The authors acknowledge a limitation of the research, which necessitates a longitudinal investigation, whereby data must be collected continuously or repeatedly over an extended duration.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Rodriguez et al 34 investigated how Design Thinking teachings influence the marginalized students' identification within computer, electrical, and software engineering programs. The results showed that marginalized students developed an identity with the surveyed courses, showing greater interest and performance.…”
Section: Related Workmentioning
confidence: 99%
“…A few engineering programs have used such expansively framed contextual tasks in the middle years with generally positive results reported (e.g., Billiar et al, 2022; Carberry & Brunhaver, 2019; Dziallas & Fincher, 2014; Froyd & Ohland, 2005; Lowe & Goldfinch, 2021; Maciejewski et al, 2017). Reports of this research commonly focus on describing instructional design and implementation and on reporting student perceptions (Hussmann & Jensen, 2007; Lowe et al, 2022; Rodriguez et al, 2020; Telenko et al, 2016), improved retention (Allen et al, 2011; Quinn, 1993), or student achievement (Froyd & Ohland, 2005; Roselli & Brophy, 2006), or on performance relative to control groups (Han et al, 2018). Little is known about how contextualized tasks that are expansively framed might lead to these positive outcomes.…”
Section: Introductionmentioning
confidence: 99%